Numerical study of variable length exhaust pipe in small engine - Mohammed, Akmal Nizam; Razali, Mohd Azahari; Sapit, Azwan; Hushim, Mohd Faisal; Osman, Shahrul Azmir; A. Rahman, Mohamad Farid (Asian Research Publishing Network (ARPN), 2017)
Small engines, with capacity not exceeding 150 cc, can be divided into two types: two-stroke and four-stroke engines. The exhaust pipe has significant influences on the performance of the engine. Thus, it is necessary to study factors that affect the exhaust in order to improve the performance of the engine. For this early stage, it would be appropriate to conduct the research by using simulations since they only require minimal resources and can be conducted in a short period. The objective of this study is to conduct the simulation for determining the required velocity and pressure in the exhaust pipe. The comparison is done between parameter values from different configuration of exhaust pipes; the most appropriate configuration is then proposed. Three types of exhaust pipe is proposed using computer software and simulations are carried out using ANSYS Workbench 15.0. Results show that the velocity and pressure fluctuate according to the diameter and length of the exhaust pipe. Model 3 exhaust pipe configurations have been selected as the most suitable exhaust pipe for obtaining the maximum pressure and velocity.